Local Food Consumption and Destination Sustainability: A Bibliometric Review of Emerging Research Trends - Indah Muthia Ayuni; Kasmita Kasmita; Yunia Wardi; Anni Faridah (ARMADA : Jurnal Penelitian Multidisiplin, 2026)
The increasing global interest in traditional food consumption highlights its strategic role in shaping cultural identity, supporting local economies, and promoting sustainable tourism. This study aims to systematically map and synthesize the determinants of traditional food consumption using a Systematic Literature Review (SLR) combined with bibliometric analysis. Data were collected from the Scopus database, resulting in 52 selected articles published between 2021 and 2026 following the PRISMA framework, while Bibliometrix in RStudio was employed to analyze publication trends, thematic structures, and research networks. The findings reveal that traditional food consumption is influenced by four key dimensions: psychological factors (attitudes and perceived value), socio-cultural factors (local identity and cultural attachment), economic factors (price and accessibility), and sustainability-related factors (environmental awareness). The study also identifies the dominance of intention-based models, particularly the Theory of Planned Behavior, alongside a persistent gap between attitudes and actual behavior. This research contributes by providing a comprehensive conceptual mapping and emphasizes the need for more integrative and interdisciplinary approaches, offering strategic insights for strengthening sustainable local food consumption, particularly in emerging economies.